อุปสรรคของรูปแบบการจัดทำและส่งมอบโครงการระบบออกแบบ-ก่อสร้าง ในการเข้าสู่ตลาดอุตสาหกรรมก่อสร้างของประเทศไทย - ณัฐพงศ์ พุ่มงาม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Design-build has been accepted as an effective project delivery system which has been popular throughout the world while in Thailand this project delivery system method is not recognized. The barriers of design-build project delivery system in entry into the construction industry market of Thailand was studied in this research. Started with in-depth interviews from experts who work as project managers for at least 10 years from both public and private sectors following by statistical analysis. The result displayed 17 possible barriers. The first three major issues were corruption, lack of experience in design-build, and risk of escalation costs. Finally the design-build model was compared to the traditional delivery method in cost-benefit perspective. A new purposed road construction project was used to evaluate these two methods by using economical approaches for construction time and cost. By using historical data combined, the result showed that design-build delivery method can be decreased construction cost of 230-500 million baht of the total cost of 3,840 million baht. Construction time can be decreased to 87 days which can be estimated to the total as 452 million baht.